Docker for cross platform - Guimar(tilde)aes Viana, Alberto; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Docker is used more and more by developers, system administrators & IT administrators every day. Originally, native to Linux it is now being adopted across all platforms. The container idea comes to simplifying application development, testing, and deployment. Using Docker, you have a unique way to package your application. We are going to start with Docker fundamentals, explaining how it works, how to set up and work with it. We will cover advanced topics such as running it on productions and build custom containers.Docker containers wrap up a piece of software in a complete filesystem that contains everything it needs to run: code, runtime, system tools, and system libraries-anything you can install on a server. This guarantees that it will always run the same, regardless of the environment it is running in. Docker Compose is a tool for defining and running multi-container Docker applications. With Compose, you use a Compose file to configure your application's services. Then, using a single command, you create and start all the services from your configuration.You will learn how to host your own Docker Registry and use it to store your images to deploy to production. This is the beginner course on Docker which covers everything required for you to run Docker on your development and production environments."--Resource description page.
Presenter, Alberto Guimar(tilde)aes Viana.
Title from title screen (viewed July 25, 2017).
Date of publication from resource description page.
Keywords: Application software -- Development; Computer software -- Development; Electronic books